Hubungan Efek Gabungan Hipertensi dan Obesitas dengan Penyakit Jantung Koroner Pada Analisis Data IFLS 5 Tahun 2014 - Pramono, Alana Arumsari; Djuwita, Ratna (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Coronary heart disease is a non-communicable disease. Risk factors for coronary heart disease include hypertension, smoking, high cholesterol, obesity, and low consumption of fruits and vegetables.Methods: The aim of this study was to determine the relationship between the combined effects of hypertension and obesity and the incidence of coronary heart disease. This study uses the 2014 Indonesia Family Life Survey (IFLS). This analysis uses univariate analysis to determine the proportion of research variables, bivariate analysis to determine the relationship between variables, and stratification analysis to determine the presence of confounding and modification effects. Multivariate analysis to determine the final model. This study used a cross-sectional design.Results: coronary heart disease variable 1.44%, hypertension and obesity 9.77%, hypertension and not obesity 9.64%, not hypertension and obesity 22.04%, not hypertension and not obesity 58.55%. And the relationship of hypertension and obesity to coronary heart disease after controlling for age and gender variables.Conclusion: The relationship of the combined effect of hypertension and obesity with the incidence of coronary heart disease after controlling for age and gender variables.